Empowering Immigrant Entrepreneurship Activities: Business Support and Cash Waqf for Immigrant Entrepreneurs Model - Binti Nor Nizam, Asiah Nadhirah; Thaker, Mohamed Asmy Bin Mohd Thas; Pitchay, Anwar Allah (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
This study aims to shed a light on how Islamic finance can play a significant role in alleviating the challenges that IE experienced and improving the accessibility to fiscal sources and social integration of the Immigrant Entrepreneurs (IE) in the host country, especially Malaysia. The prominent challenges that the IEs are facing are the difficulties in accessing the capital to finance their business and the lack of knowledge of the local regulations. The findings lead to a model that aims to tackle the challenges that IE experienced via Business Support and Cash Waqf for IE Model (BS-WIEM). The BS-WIEM acts as a comprehensive initiative to bridge the resource disparity among IE in terms of funding accessibility and human capital development. This study attempts to construct the BS-WIEM based on the extensive literature review related to the challenges the IE experienced and waqf. This research can positively impact the development and funding of the IE in Malaysia. This study will provide insights to the government, waqf institutions, corporations, financial institutions, and policymakers about alternative funding options for IE businesses and start-ups in the host country. Less tension on the public spending by the government with the involvement of non-profit organizations. This conceptual paper only explores the literature; thus, no empirical analysis is available. More in-depth and comprehensive insights could be identified with the empirical studies. Future research on the regulatory and shariah perspective of the model should be done. The findings of this paper will offer a cash waqf model as an alternative to fund the development of entrepreneurship in Malaysia, especially for immigrants.